Preliminary study of a control algorithm for radio-frequency-induced intestinal tissue fusion - Tu, Liangyong; Zhou, Yu; Song, Chengli; Li, Yuan; Chen, Lin; Xue, Yinmin (International journal of hyperthermia, 2019)
Purpose: A control algorithm for radio-frequency-induced intestinal tissue fusion was developed to explore the effects of different control parameters on intestinal tissue fusion. Materials and methods: Radio-frequency-induced fusion was performed on ex vivo small intestine tissue. The effect on the fusion was observed by changing the control parameters (power, interval time, and terminal impedance) in the algorithm. The quality of fusion was evaluated using the burst pressure and thermal damage measurement. Histological evaluation was used to assess the fusion quality indirectly. Results: A maximum burst pressure of 8.460 ± 0.2674 KPa was acquired when the power was set to 100 W, the interval time was set to 2000 ms, and the terminal impedance was set to 50 Ω. Moreover, the thermal damage range increased with an increase in power but decreased with an increase in the interval time and terminal impedance. Furthermore, the thermal damage range and temperature were presumably related. Conclusions: For an ex vivo small intestine tissue, the appropriate control parameters could be set when the power was approximately 100 W, the interval time was approximately 2000 ms, and the terminal impedance was approximately 50 Ω. This study could provide a basis for the selection of control parameters for intestinal tissue fusion.